Step * 1 2 of Lemma qexpfact-property


1. : ℕ
2. ∀d:ℕd
     ∀[n:ℕ]. ∀[x:{q:ℚ0 ≤ q} ]. ∀[p:ℚ]. ∀[b:{b:ℤ(n)! ∈ ℤ].
       (((qexpfact(n;x;p;b) n) ≤ d)  x ↑ qexpfact(n;x;p;b) n < (qexpfact(n;x;p;b))!)
3. : ℕ
4. {q:ℚ0 ≤ q} 
5. : ℚ
6. : ℤ
7. ¬p < b
8. (n)! ∈ ℤ
⊢ ((eval n' in
    eval p' in
    eval b' n' in
      qexpfact(n';x;p';b') n) ≤ d)
 x ↑ eval n' in eval p' in eval b' n' in   qexpfact(n';x;p';b') n < (eval n' in
                                                                                               eval p' in
                                                                                               eval b' n' in
                                                                                                 qexpfact(n';x;p';b'))!
BY
(RepeatFor ((CallByValueReduce THENA Auto)) THEN Subst' (n 1) (n 1)! 0) }

1
.....equality..... 
1. : ℕ
2. ∀d:ℕd
     ∀[n:ℕ]. ∀[x:{q:ℚ0 ≤ q} ]. ∀[p:ℚ]. ∀[b:{b:ℤ(n)! ∈ ℤ].
       (((qexpfact(n;x;p;b) n) ≤ d)  x ↑ qexpfact(n;x;p;b) n < (qexpfact(n;x;p;b))!)
3. : ℕ
4. {q:ℚ0 ≤ q} 
5. : ℚ
6. : ℤ
7. ¬p < b
8. (n)! ∈ ℤ
⊢ (n 1) (n 1)!

2
1. : ℕ
2. ∀d:ℕd
     ∀[n:ℕ]. ∀[x:{q:ℚ0 ≤ q} ]. ∀[p:ℚ]. ∀[b:{b:ℤ(n)! ∈ ℤ].
       (((qexpfact(n;x;p;b) n) ≤ d)  x ↑ qexpfact(n;x;p;b) n < (qexpfact(n;x;p;b))!)
3. : ℕ
4. {q:ℚ0 ≤ q} 
5. : ℚ
6. : ℤ
7. ¬p < b
8. (n)! ∈ ℤ
⊢ ((qexpfact(n 1;x;x p;(n 1)!) n) ≤ d)
 x ↑ qexpfact(n 1;x;x p;(n 1)!) n < (qexpfact(n 1;x;x p;(n 1)!))!


Latex:


Latex:

1.  d  :  \mBbbN{}
2.  \mforall{}d:\mBbbN{}d
          \mforall{}[n:\mBbbN{}].  \mforall{}[x:\{q:\mBbbQ{}|  0  \mleq{}  q\}  ].  \mforall{}[p:\mBbbQ{}].  \mforall{}[b:\{b:\mBbbZ{}|  b  =  (n)!\}  ].
              (((qexpfact(n;x;p;b)  -  n)  \mleq{}  d)  {}\mRightarrow{}  p  *  x  \muparrow{}  qexpfact(n;x;p;b)  -  n  <  (qexpfact(n;x;p;b))!)
3.  n  :  \mBbbN{}
4.  x  :  \{q:\mBbbQ{}|  0  \mleq{}  q\} 
5.  p  :  \mBbbQ{}
6.  b  :  \mBbbZ{}
7.  \mneg{}p  <  b
8.  b  =  (n)!
\mvdash{}  ((eval  n'  =  n  +  1  in
        eval  p'  =  x  *  p  in
        eval  b'  =  n'  *  b  in
            qexpfact(n';x;p';b')  -  n)  \mleq{}  d)
{}\mRightarrow{}  p  *  x  \muparrow{}  eval  n'  =  n  +  1  in  eval  p'  =  x  *  p  in  eval  b'  =  n'  *  b  in      qexpfact(n';x;p';b')  -  n 
      <  (eval  n'  =  n  +  1  in
            eval  p'  =  x  *  p  in
            eval  b'  =  n'  *  b  in
                qexpfact(n';x;p';b'))!


By


Latex:
(RepeatFor  3  ((CallByValueReduce  0  THENA  Auto))  THEN  Subst'  (n  +  1)  *  b  \msim{}  (n  +  1)!  0)




Home Index